2017
DOI: 10.1590/s0102-865020170040000001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract of the leaves of Baccharis trimera on the proliferation of hepatocytes after partial hepatectomy in rats

Abstract: DAdministration of aqueous extract of the leaves of Baccharis trimera 100 mg/kg of animal has a significant positive effect on liver regeneration in rats, 24 hours after hepatectomy (70%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…Preclinical studies of B. trimera reported hypocholesterolemic, antiinflammatory, antiulcerogenic, antifungal, antibacterial, antiallergic, and anticarcinogenic activity (Alonso 1998, Lívero et al 2016a, Lima et al 2017. B. trimera also decreases adipogenesis and has antioxidant activity that can reduce lipid peroxidation, endothelial dysfunction, and cholesterol oxidation, a limiting step in the development of atherosclerosis (Pádua et al 2010, Hurrell et al 2015, Sabir et al 2017, Nascimento et al 2017.…”
Section: An Acad Brasmentioning
confidence: 99%
“…Preclinical studies of B. trimera reported hypocholesterolemic, antiinflammatory, antiulcerogenic, antifungal, antibacterial, antiallergic, and anticarcinogenic activity (Alonso 1998, Lívero et al 2016a, Lima et al 2017. B. trimera also decreases adipogenesis and has antioxidant activity that can reduce lipid peroxidation, endothelial dysfunction, and cholesterol oxidation, a limiting step in the development of atherosclerosis (Pádua et al 2010, Hurrell et al 2015, Sabir et al 2017, Nascimento et al 2017.…”
Section: An Acad Brasmentioning
confidence: 99%
“…Liver cells respond positively to some herbal drugs. These include Baccharis trimera, picroliv, ellagic acid and curcumin 4,5 . The positive effects of TQ on liver are also known [6][7][8] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…[55] The animals that received a single dose of CCl 4 after 15 days of oral treatment with the extract at doses of 300 and 600 mg/kg showed a dose-dependent decrease in ALT activity, lipid peroxidation and protein carbonylation in liver tissue. Lima et al [57] demonstrated the restoration of liver mass in rats administrated with an infusion obtained from leaves of B. crispa (100 mg/ kg, p.o. ), 24 h after undergoing a partial hepatectomy.…”
Section: Baccharis Crispa Sprengmentioning
confidence: 99%
“…In Brazil, several plants with an intense bitter taste are used in folk medicine as tonics for digestive system functions, and they are included in phytomedicines prepared by local laboratories and in home remedies. [149] Moreover, the Brazilian population has a long history of using bitter medicinal plants to relieve liver diseases, including the widely-distributed species B. crispa and Phyllanthus niruri L. [57] Twenty-two species were listed in the present work as bitter tonics, among which the Simaroubaceae family accounted for four species: Quassia amara L. ('quina'), [25][26][27][28]40,41] Simaba ferruginea A.St.-Hil. ('calunga'), [11,25] Coutarea hexandra (Jacq.)…”
Section: Quassia Amara Lmentioning
confidence: 99%